Assessment of the Nutritional Benefits and Aflatoxin B1 Adsorption Properties of Blackberry Seed Cold-Pressed Oil By-Product - Jelena Miljanić; Saša Krstović; Lidija Perović; Jovana Kojić; Vanja Travičić; Branimir Bajac (Foods)
This study explores the potential valorization of blackberry seed oil cake (BBSOC), a by-product of cold-pressed blackberry seed oil (Rubus fruticosus L.), as a nutritionally valuable material with aflatoxin B1 (AFB1) adsorption properties. The chemical and mineral composition, polyphenols, and antioxidant activity of BBSOC flour were assessed. BBSOC was found to be a significant source of fiber (62.09% dry weight) and essential minerals such as Fe (123.48 mg/kg), Mg (1281.40 mg/kg), K (3087.61 mg/kg), and Ca (1568.41 mg/kg). The high polyphenol content, especially ellagic acid, highlighted its biologically active potential. Moreover, BBSOC demonstrated effective biosorption of AFB1 under in vitro conditions at 37 °C, with adsorption efficiencies of 85.36% and 87.01% at pH 3 and 7, respectively. Characterization techniques including SEM, FTIR analysis, Boehm titration, and pH zero charge determination confirmed its AFB1 adsorbing properties. This valorization process reintroduces a secondary product into the food chain, supporting the circular economy and zero-waste concepts. Thus, BBSOC is nutritionally rich and effective in AFB1 biosorption, presenting potential applications as a food or feed additive.